Penerapan Multimedia Interaktif Berbasis Peta Konsep Guna Meningkatkan Hasil Belajar Siswa Kelas Vii Mts Ma'arif Al-Ishlah Bungkal Dalam Pembelajaran SKI - Ajeng Mustikasari, Rika; Mustofa, Zamzam; Mukminin, Amir (LP3M STAI Ibnurusyd, 2023)
This study focuses on the use of interactive Multimedia concept map-based to determine the resultsin improving the learning outcomes of Class VII students. The purpose of this study was to determinewhether there is an increase in learning outcomes of students in grade VII before and after using theconcept map media. The method used is qualitative research with a case study approach with datacollection techniques, namely interviews, recordings, observations and data analysis. The resultsshowed a significant difference in students between before and after using the concept map learningmedia.